Activated residue soil alkali-activated concrete preparation method and superposed beam
By activating the slag alkali to stimulate the concrete preparation method, and using the engineering slag and ore powder to react with the alkali trigger, the problems of high energy consumption and environmental pollution in the traditional concrete preparation process are solved, and low-cost, high-strength and green-environmental concrete preparation is achieved.
Patent Information
- Application Number
- CN202411696026.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-04-08
AI Technical Summary
There are problems of high energy consumption, environmental pollution and resource waste in the preparation process of existing concrete, especially in the cement production process, which consumes a large amount of natural resources and emits a large amount of CO2.
The preparation method of activated slag alkali-activated concrete is adopted to treat engineering slag by crushing, calcining and crushing, combining ore powder and alkali exciter to form high-performance concrete, reducing dependence on traditional cement.
It has achieved low-cost, high-strength and green environmentally friendly concrete preparation, reduced energy consumption and environmental pollution, effectively utilized engineering waste resources, and reduced the damage to the environment by cement production.
Smart Images

Figure FT_1 
Figure FT_2 
Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and in particular relates to a method for preparing activated slag alkali-activated concrete and a composite beam. Background Art
[0002] With the rapid development of urbanization and the shortage of land resources, my country has developed and utilized underground space on a large scale, resulting in a sharp increase in the stock of construction waste, accounting for nearly 60% of the total construction and demolition waste. Most of the construction waste is transported to landfills, which wastes high transportation costs and causes urban traffic jams, environmental pollution, and safety hazards. Portland cement concrete is the main material in construction at present. Cement is made by grinding and calcining limestone. The production process wastes a lot of natural resources and produces a lot of CO2, which seriously pollutes the environment. Slag is an industrial by-product produced by the metal smelting industry. If it is not handled properly, it is easy to cause soil and water pollution. Slag has the potential to replace cement as a cementitious material under the action of alkaline activators, but too high a slag content will reduce the strength of concrete and easily cause sedimentation and water segregation, thereby limiting its application. In addition, Na2O·nSiO2 in traditional alkaline activators requires a lot of energy in its production process, which undoubtedly increases CO2 emissions.
[0003] With the rapid development of urban construction, more and more buildings need to use natural aggregates to produce lightweight concrete. Due to the shortage of natural resources, the cost remains high. Therefore, it is necessary to develop a concrete that can produce low cost, high strength, good working performance, and green environmental protection, so as to meet the use needs of different construction projects. Summary of the invention
[0004] The purpose of the present invention is to overcome the shortcomings involved in the above concrete preparation process and provide a method for preparing activated slag alkali-activated concrete.
[0005] The present invention adopts the following technical solutions: The method for preparing activated slag alkali-activated concrete comprises the following steps: S1. Use a crusher to crush large pieces of construction slag, and use a pulverizer to grind them into slag powder after drying; Specifically, use a crusher to crush large pieces of construction slag into appropriate sizes, and remove moisture by drying to ensure the efficiency and quality of subsequent crushing and grinding. Use a pulverizer to further grind the dried slag into powder to ensure the fineness and uniformity of the slag powder, which is conducive to subsequent activation treatment and concrete preparation.
[0006] S2, calcining the slag powder in step S1 to form activated slag, and mixing the activated slag with mineral powder and reinforcing agent to form a mixture; specifically, calcining the slag powder to change its physical and chemical properties and improve its activity. The activated slag is evenly mixed with the mineral powder and reinforcing agent to form a mixture with certain strength and performance.
[0007] S3, mixing calcium hydroxide, water glass and water to form an alkaline activator; specifically, water glass as an alkaline activator can increase the activity of the powder, and then polymerize to form an inorganic gelling material having a three-dimensional network bonding structure of Si, Al and O; S4, premixing the mixture of step S2 with the alkali liquor activator of step S3 to form a geopolymer slurry, adding sand and gravel to stir to form concrete. Specifically, the premixing process helps the initial geopolymer reaction and improves the uniformity and performance of concrete. Add appropriate amounts of sand and gravel as aggregates to the geopolymer slurry, stir well to form concrete. Compared with traditional silicate cement concrete, the preparation process of this activated slag alkali-activated concrete reduces the dependence on cement, thereby reducing the environmental pollution caused by cement production.
[0008] Specifically, slag (also called granulated blast furnace slag) is a loose, porous granular material formed by the rapid cooling of minerals floating on the surface of pig iron in water when blast furnace slag is used to smelt pig iron. Slag is an industrial byproduct produced in the process of producing pig iron. Processing industrial waste slag into mineral powder and reusing it can reduce waste slag emissions and environmental pollution, which meets the requirements of sustainable development. Its ingredients include volcanic ash, fly ash, and silica fume, which can replace part of cement in concrete production. At the same time, mineral powder also has the advantages of improving fluidity, workability, durability and mechanical properties of concrete, and improving concrete's resistance to sulfates and seawater corrosion.
[0009] Specifically, the mineral powder is obtained by processing the slag through dry grinding, airflow classification, and screening to obtain slag powder with uniform particle size. The mineral powder contains about 46% calcium oxide, 24% silicon dioxide, and 22% aluminum oxide. The mineral powder can effectively improve the compressive strength of concrete and reduce the cost of concrete; at the same time, it has obvious effects on inhibiting alkali-aggregate reaction, reducing hydration heat, reducing early temperature cracks in concrete structures, improving concrete density, and improving impermeability and erosion resistance. The utilization of industrial by-product mineral powder also avoids soil and water pollution caused by improper treatment of these by-products. Its rational application in concrete preparation is an environmentally friendly treatment method that reduces the potential harm of industrial waste to the environment.
[0010] Specifically, geopolymer concrete itself has the advantages of low hydration heat, good antifreeze performance, strong corrosion resistance, etc. The concrete prepared by the present invention can give full play to these advantages of geopolymer concrete through the combination of activated slag and alkali activator and other components, so that the prepared concrete has better durability in complex engineering environments (such as cold areas, environments with corrosive media, etc.), reducing the maintenance and replacement costs caused by poor concrete performance. Using engineering slag as the main raw material reduces the cost of raw materials. The engineering slag in this method can partially replace natural aggregates, reduce the dependence on expensive natural aggregates, thereby reducing the production cost of concrete, and has certain economic advantages.
[0011] Furthermore, the construction slag in step S1 is crushed to a particle size of less than 10 mm, and the slag powder is ground to a particle size of less than 0.75 mm. When the particle size of the slag powder is ground to less than 0.75 mm, its specific surface area will be significantly increased. During the calcination process, the slag powder can be more fully exposed to heat and heated more evenly, which helps to improve the calcination efficiency and activate the slag more effectively, thereby better playing its role in the subsequent formation of high-performance concrete.
[0012] Specifically, for the subsequent operations of mixing with mineral powder and reinforcing agent to form a mixture and pre-mixing with alkali activator to form geopolymer paste, the slag powder with smaller particle size can be better mixed with other materials evenly to avoid agglomeration caused by excessively large particle size, so that the synergistic effect between the components can be fully exerted, thereby ensuring the quality stability of the geopolymer paste and the final concrete.
[0013] Specifically, the crushed and finely ground slag has a particle size that is more suitable for participating in the hydration and other reaction processes of concrete. During the setting and hardening of concrete, these fine and uniform slag particles can better fill the gaps between other aggregates (such as sand, gravel, etc.), making the internal structure of concrete more compact, which in turn helps to improve the concrete's compressive and flexural strength indicators, allowing the prepared activated slag alkali-activated concrete to better meet the strength requirements of various engineering structures.
[0014] Specifically, finer slag powder helps improve the working properties of concrete, such as better workability. During the mixing process, it can make the fluidity of concrete more suitable, which is convenient for construction operations. Whether it is pouring, vibrating, etc., it can be carried out more smoothly, reducing construction defects caused by poor concrete working performance and ensuring project quality.
[0015] Furthermore, the crushed stone is made of granite crushed stone and slag crushed stone, which are mixed in a mass ratio of 1:1, and the crushed stone particle size is between 5-15mm; the sand is graded sand and gravel, and the particle size is less than 3.6mm. Granite crushed stone has high hardness and strength, and its own dense structure can provide good bearing capacity for concrete, which helps to improve the overall mechanical properties of concrete such as compressive strength and flexural strength. The slag crushed stone comes from engineering slag. After activation and other treatments, it can better react with geopolymer cementitious materials to enhance the cementing properties inside the concrete. The two are mixed in a mass ratio of 1:1, which can complement each other, so that the concrete has sufficient strength while the integrity and stability of the internal structure can be optimized. It can not only better meet the requirements for concrete strength in different engineering scenarios, but also improve the durability indicators of concrete such as impermeability, and extend the service life of the engineering structure.
[0016] Specifically, limiting the crushed stone particle size to between 5-15mm and combining it with graded sand and gravel with a particle size of less than 3.6mm can form a good particle grading system. There will be certain gaps between the larger-sized crushed stone particles, while the smaller-sized graded sand and gravel can effectively fill these gaps, making the internal structure of the concrete more compact. At the same time, the addition of slag and crushed stone can also participate in the process of gap filling, further reducing the void ratio and improving the density of the concrete, which is not only helpful for improving strength, but also can effectively reduce the permeability of concrete, enhance its anti-seepage, anti-freeze and other properties, and improve the adaptability of concrete in complex environments.
[0017] Specifically, during the mixing process, gravel and sand of different particle sizes can cooperate with each other, so that the concrete has appropriate fluidity, which is convenient for pouring, vibrating and other operations during construction, ensuring that the concrete can be evenly filled into the mold or engineering structure, reducing the occurrence of segregation, water seepage and other phenomena, and ensuring the quality of engineering construction.
[0018] Furthermore, the calcination method of activated slag comprises the following steps: M1. The ground slag powder is placed in a muffle furnace and heated from 20°C to 800°C at an average speed of 10°C per minute, and maintained at 800°C for 2.0 hours; the gradual heating method allows the slag powder particles to gradually absorb heat, and some mineral crystal structures can be gradually destroyed and reorganized in a relatively mild and orderly heating environment, so that the originally bound active ingredients can be released and more fully activated, which is conducive to better reaction with other materials in the subsequent concrete preparation, improving the gelling properties of the geopolymer, and thus enhancing the overall performance of the activated slag alkali-activated concrete.
[0019] Specifically, maintaining this high temperature for 2.0 hours after heating to 800°C can ensure that the slag powder is at a suitable activation temperature for a sufficiently long time. Long-term high temperature can further promote the activation of active components such as silicate in the slag, so that their activity reaches a higher level, increase their ability to participate in the subsequent alkali-induced reaction to generate geopolymers, help form a more stable and high-performance geopolymer network structure, and improve the strength, durability and other key performance indicators of concrete.
[0020] M2. After heating is completed, wait for the temperature in the muffle furnace to cool naturally to 20°C to form calcined activated slag. The natural cooling method avoids the damage to the activated slag structure caused by sudden cooling. Sudden cooling will cause cracks and deformation in some stable structures that have been activated and formed, affecting their subsequent performance in concrete. The natural cooling process is relatively slow, which allows the internal structure of the activated slag to adjust and stabilize in an orderly manner as the temperature gradually decreases, maintaining its good activity state and physical and chemical structural integrity, thereby ensuring that it can play a stable role when mixed with mineral powder, alkali activator, etc. to prepare concrete.
[0021] Furthermore, the ratio of calcium hydroxide, water glass and water is 10-20:40-50:30-50 calculated by mass ratio. Calcium hydroxide, as an alkaline substance, can provide sufficient alkalinity to stimulate the active ingredients in slag and mineral powder at an appropriate ratio. The sodium silicate and other components in the water glass interact with calcium hydroxide to promote the dissolution and polymerization of substances such as aluminosilicates. The appropriate ratio ensures that there is enough alkali to start and maintain the reaction, so that the generated geopolymer gel has good stability and gelling properties, and does not cause excessively violent reactions or the generation of undesirable products such as ettringite due to excessive alkalinity, which helps to form a stable geopolymer network structure and improve the durability of concrete.
[0022] Specifically, water in the mass ratio range of 30-50 can make the alkali activator have a suitable consistency, and when it is stirred with the mixture for 15 minutes to form a geopolymer paste, it can provide suitable fluidity for the paste. Too low a water ratio will cause the paste and concrete to be too viscous and difficult to construct, while too high a water ratio will cause problems such as segregation and bleeding, affecting the quality and performance of the concrete.
[0023] Specifically, by adjusting the ratio of calcium hydroxide, water glass and water, the setting time of concrete can be adjusted to a certain extent. Appropriate alkalinity and water content can control the polymerization reaction speed of geopolymer, so that it can meet the construction operation time requirements while ensuring that the concrete can set and harden in time after pouring, avoiding construction problems caused by too long or too short setting time.
[0024] Furthermore, activated slag, mineral powder and reinforcing agent are mixed in a mass ratio of 6:3:1 to form a mixture. The activated slag reacts with alkali to provide partial cementitious properties and filling effects for the concrete. As an industrial by-product, the mineral powder itself contains active ingredients such as silicate and aluminate. Under the action of the alkali activator, it can form a good cementitious material, which helps to improve the strength and durability of the concrete. The reinforcing agent can further promote the improvement of this cementitious network, enhance the bonding force between the cementitious material and the aggregate, and improve the compressive and flexural strength indicators of the concrete, so that it can more effectively disperse stress when bearing external forces and improve the overall structural stability. Mixing in a ratio of 6:3:1 can give full play to the advantages of the three, so that they can cooperate with each other to jointly improve the comprehensive performance of the mixture and the final prepared concrete.
[0025] Specifically, a relatively large proportion of activated slag is used as the main component, which makes full use of the waste resource of engineering slag that originally requires a large amount of treatment, reduces the dependence on other expensive raw materials such as natural aggregates, and conforms to the concept of resource recycling. At the same time, the appropriate amount of mineral powder is added to reasonably apply industrial by-products to avoid the environmental pollution problems caused by them. At the same time, the cost of raw materials can be effectively controlled, making the final activated slag alkali-activated concrete suitable for engineering construction projects.
[0026] Furthermore, the weight ratio of the mixture, sand, crushed stone and alkali activator is 0.8-1.2:1.5-2.0:2.5-3.5:0.25-0.75, and the reinforcing agent includes at least three of carbon fiber, steel fiber, waste shell powder, rubber powder, glass fiber, retarder and water reducer.
[0027] Specifically, the mixture, sand and gravel are matched in a certain proportion to form a tightly packed structure. The activated slag and mineral powder in the mixture produce gelling properties under the action of the alkali activator and fill the gaps between the sand and gravel. When the ratio of sand to gravel is between 1.5-2.0 and 2.5-3.5, it cooperates with the mixture to make the skeleton structure inside the concrete more stable. Gravel provides the main support as coarse aggregate, sand fills the larger gaps between gravel, and the mixture further fills the tiny gaps and provides bonding force. Such a structure can effectively resist external loads and improve the compressive and flexural strength of concrete.
[0028] Specifically, the proportion range of the mixture, sand and gravel can reduce the porosity inside the concrete and improve its density. The dense structure helps to prevent the intrusion of harmful substances from the outside (such as moisture and chemically corrosive substances), enhance the durability of concrete, and extend the service life of the concrete structure. This proportion range can ensure that the concrete has good workability. It ensures that the concrete can be smoothly formed during the construction process, and the surface quality of the concrete after forming is smooth and flat. The concrete is easy to operate during the mixing process and has appropriate fluidity, which is convenient for pouring, vibrating and other operations during construction. If the proportion of sand or gravel is too high, the concrete will be too dry, poor in fluidity, and difficult to construct; and if the proportion of the mixture is too high, the concrete will be too viscous, which will also affect the construction quality.
[0029] Specifically, the alkali activator can provide a sufficient alkaline environment for the activated slag and mineral powder in the mixture within the ratio range of 0.25-0.75, and promote the alkali activation reaction. The main components of the alkali activator, such as calcium hydroxide and water glass, can activate the active components in the slag and mineral powder, causing them to polymerize to form geopolymer gel. The appropriate alkali activator ratio can control the reaction rate, ensure that the reaction is fully carried out, and form high-quality geopolymer gelling materials. If the alkali activator ratio is too low, the active components cannot be fully activated, affecting the strength and durability of the concrete; while a high ratio will cause the reaction to be too fast, generate unstable products, and also increase the cost. At the same time, the alkali activator can also affect the water retention of concrete, prevent the bleeding of concrete during the construction process, and ensure the uniformity of the quality of the concrete. The alkali activator can adjust the setting speed of the concrete, so that it can not only meet the requirements of sufficient operation time during the construction process, but also set and harden as soon as possible after pouring, thereby improving the construction efficiency.
[0030] Specifically, the steel fiber includes a corrugated steel fiber or a fine steel fiber with a diameter between 0.1 and 0.3 mm. The corrugated steel fiber can increase the contact area with the cement base material and improve the bonding force. The fine steel fiber plays a role in bridging cracks in concrete. When the concrete is subjected to tension, the steel fiber can bear part of the tension and prevent the expansion of the cracks.
[0031] Specifically, steel fibers can effectively improve the tensile strength of concrete when accounting for 1%-1.5% of the total mass of the net paste, water, and coarse and fine aggregates. In some bending members such as beams and slab structures, the addition of steel fibers can significantly enhance the ability of concrete to resist bending and tensile damage, allowing the structure to withstand greater loads without brittle fracture. When the concrete structure is subjected to shear force, steel fibers can resist shear deformation through the bonding force with the concrete matrix. This is very important for structural members such as columns and shear walls that are subjected to large horizontal shear forces. Adding an appropriate amount of steel fibers can significantly improve the shear resistance of concrete and enhance the stability of the structure under horizontal forces such as earthquakes and wind loads. The presence of steel fibers gives concrete better toughness and can absorb more impact energy. Steel fiber concrete reduces damage and spalling on the concrete surface by resisting impact, thereby extending the service life of the structure. Since steel fibers can limit the development of cracks, they can reduce the intrusion of harmful substances such as moisture and chloride ions, thereby reducing the risk of durability problems such as steel bar corrosion and freeze-thaw damage in concrete.
[0032] Specifically, in some harsh environmental conditions, such as marine environment, chemical corrosion environment, etc., steel fiber concrete can better maintain the integrity of the structure. Because it improves the mechanical properties of concrete, it also indirectly enhances the resistance of the structure to environmental erosion, so that the concrete structure can maintain good performance during long-term use. Steel fibers accounting for 1%-1.5% of the total mass of the net slurry, water, and coarse and fine aggregates can provide sufficient restraint. Because the steel fibers are tightly bonded to the concrete matrix, the relative displacement of the internal particles of the concrete is limited, thereby reducing the structural deformation and even cracking caused by shrinkage and creep. The right amount of steel fibers can be evenly distributed during the concrete mixing process, and will not cause a significant deterioration in the working performance of the concrete. Moreover, during the concrete pouring process, steel fibers can help maintain the shape stability of the concrete, prevent local collapse or excessive deformation of the concrete during the vibration process, and ensure the smooth progress of the concrete construction.
[0033] Specifically, in the long run, adding steel fibers will improve the mechanical properties and durability of concrete, reduce the number of repairs and reinforcements during the use of the structure, and thus reduce the cost of the entire life cycle. Using steel fibers at a ratio of 1%-1.5% of the total mass of the net slurry, water, and coarse and fine aggregates can give full play to its reinforcing effect without significantly increasing the amount of steel fibers, achieving the purpose of economical and rational use of resources, so that the concrete can meet the performance requirements while reducing costs as much as possible.
[0034] Specifically, carbon fiber includes polyacrylonitrile-based carbon fiber or asphalt-based carbon fiber, and carbon fiber has excellent mechanical properties such as ultra-high strength and modulus. Carbon fiber evenly dispersed in concrete can effectively share the load borne by concrete like "tendons and bones", and significantly improve the mechanical performance indicators of concrete such as tensile strength, flexural strength and impact toughness. In the case where the structure is subjected to tension, bending or impact, carbon fiber can inhibit the generation and expansion of cracks, enhance the overall toughness of the concrete structure, and make the structure more durable, especially suitable for some construction projects with high requirements for earthquake resistance and impact resistance. The addition of carbon fiber can also improve the durability and stability of concrete. It can prevent the intrusion of external corrosive media such as chloride ions and sulfates to a certain extent, and delay the deterioration process of concrete. At the same time, due to its good chemical stability, it can also maintain its own performance stability under complex environmental conditions, thereby improving the long-term service capacity of the entire concrete structure, reducing the number of repairs and replacements, and reducing the cost of the entire life cycle.
[0035] Specifically, the waste shell powder includes oyster shells and scallop shells. Specifically, the collected shells are first soaked and cleaned with an alkaline solution. Soaking the shells in a sodium hydroxide solution can effectively remove dirt, algae and organic residues on the surface of the shells, improve the purity of the shells and the effect of subsequent treatment. The concentration of the alkaline solution is 1M / L, and the soaking time is 1-2 hours to avoid damage to the shell structure and ensure effective cleaning. Then the cleaned shells are broken into shell particles and dried. The broken shells are easy to grind and process. Drying is to remove moisture from the shells to prevent agglomeration during the grinding process or uneven thermal expansion in subsequent processing. The broken shell particles are dried to ensure that the moisture content in the shell particles is minimized. The shell particles are ground into shell powder by ball milling; ball milling can grind the shell particles into fine powder, increase the specific surface area of the shell powder, and improve its dispersibility and reactivity in the composite material. Calcine at a temperature of 800°C to 1000°C for 2 hours and set aside. High-temperature calcination can completely remove organic matter in the shells, such as proteins and carbohydrates, and at the same time convert the calcium carbonate in the shells into calcium oxide, thereby improving the chemical and thermal stability of the shell powder.
[0036] Specifically, the preparation method of shell powder effectively improves the purity, fineness and stability of shell powder through the steps of soaking and cleaning, crushing and drying, ball milling and calcining. The spare discarded shell powder particles can play a certain lubricating role in the mixing process of materials such as concrete, improve the fluidity of the material, and facilitate construction operations. It can be filled in the tiny gaps between cement particles and aggregates to make the internal structure of the material more compact, which helps to improve the compressive strength and impermeability of the material. In addition, the discarded shell powder comes from shell waste, and it is used as a reinforcing agent to realize the reuse of waste resources and reduce the pollution of shell garbage to the environment, which is in line with the concept of sustainable development and environmental protection. Shell powder contains ingredients such as calcium carbonate. In an alkaline environment, it may react with cement hydration products to generate some substances with gelling properties, further enhancing the overall strength of the material.
[0037] Specifically, the rubber powder used is 80 mesh tire rubber powder, which can reduce resource waste while having good elasticity and toughness. After being added to the material, when the material is impacted by external force, the rubber powder can absorb and disperse the impact energy through its own elastic deformation, effectively improving the material's impact resistance, making it less likely to crack, break, or be damaged by sudden impact. It can give the material a certain degree of flexibility, reduce the brittleness of the material, and make the material less likely to have brittle fracture when it is deformed under load, but have a certain degree of elastic deformation ability.
[0038] Specifically, glass fiber includes alkali-resistant glass fiber or short-cut glass fiber, which has high strength and modulus. After being added to the material, it can bear part of the load like "tendons and bones", significantly improving the tensile strength and flexural strength of the material. In concrete, glass fiber can effectively resist the expansion of cracks caused by tension, making the material less likely to be damaged when subjected to bending, stretching and other loads, and enhancing the overall bearing capacity of the structure. It can form a randomly distributed fiber reinforcement network inside the material. When the material has microcracks due to shrinkage, temperature changes or stress, the glass fiber can cross the cracks to prevent further expansion of the cracks, improve the material's crack resistance, and ensure the integrity and durability of the material structure.
[0039] Specifically, due to the inhibitory effect of glass fiber on crack expansion, the channels for harmful substances from the outside (such as moisture, chemically corrosive substances, etc.) to intrude into the material through cracks are reduced, thereby enhancing the material's resistance to environmental erosion and extending the material's service life. The presence of glass fiber can constrain the relative displacement of particles inside the material, help reduce shrinkage deformation, creep and other phenomena during the hardening process of the material, improve the dimensional stability of the material, and ensure that the structure will not affect its function due to excessive deformation during long-term use.
[0040] Specifically, the retarder includes one of calcium ethylenediaminetetramethylenephosphonate, sodium carboxymethylcellulose, and sodium gluconate, and the retarder can delay the coagulation and hardening process of the material. During the construction of some large-scale projects or in high-temperature environments, materials such as concrete may coagulate too quickly, resulting in difficulties in construction operations. After adding the retarder, the initial and final setting times of the material can be appropriately extended according to actual construction needs, so that construction personnel have more time to perform operations such as mixing, transportation, pouring, and vibration to ensure construction quality. The retarder slows down the hydration rate of cement, making the heat release smoother, reducing the possibility of cracks in the concrete due to temperature stress, and improving the integrity and durability of large-volume concrete structures.
[0041] Specifically, the water reducer includes one of calcium lignin sulfonate, a polycarboxylic acid water reducer with a main chain of methacrylic acid and methyl acrylate copolymer and a side chain of polyoxyethylene. The water reducer can reduce the water-cement ratio in the material concrete, and can reduce the amount of water while maintaining the same fluidity. It effectively avoids the occurrence of adverse phenomena such as segregation and water seepage in the material, and ensures the uniformity and quality of construction. The water reducer reduces the water-cement ratio, reduces the porosity inside the material, and makes the structure more compact. After the cementitious materials such as cement are hydrated, more and denser hydration products can be formed, thereby improving the mechanical properties of the material such as compressive strength and flexural strength, and by reducing the channels for external moisture, chemically corrosive substances, etc. to enter the material, the material's resistance to durability problems such as freeze-thaw cycles and chemical corrosion is enhanced, the service life of the material is extended, and its stability for long-term use under different environmental conditions is improved. On the basis of maintaining the working performance and strength requirements of the material, the use of the water reducer can appropriately reduce the amount of cement, which not only helps to reduce production costs, but also reduces the consumption of natural resources and the emission of pollutants such as carbon dioxide during cement production.
[0042] Further, calcium hydroxide comprises the following preparation steps: N1. Limestone particles are sent from the raw material bin to the preheater for heat exchange with the high-temperature exhaust gas from the calcining furnace to increase the temperature of the limestone; limestone particles are first sent to the preheater for heat exchange with the high-temperature exhaust gas from the calcining furnace, which can make full use of the heat carried by the exhaust gas discharged from the calcining furnace. Originally, the heat of these exhaust gases would be directly dissipated into the environment, causing energy waste. However, through heat exchange, the limestone can absorb part of the heat in advance, the temperature is increased, and the waste heat of the exhaust gas is effectively recovered, which reduces the energy consumption required for subsequent rotary kiln heating of limestone, and improves the overall energy utilization efficiency, which is in line with the production concept of energy conservation and emission reduction.
[0043] Specifically, the preheated limestone already has a certain initial temperature when it enters the rotary kiln. Compared with directly sending room temperature limestone into the rotary kiln, it can reach the temperature conditions required for the decomposition reaction more quickly, shortening the time to reach the reaction temperature in the rotary kiln, thereby improving the production efficiency of the entire calcium hydroxide production process, allowing more calcium hydroxide products to be produced per unit time, meeting the subsequent demand for use as an alkali activator raw material.
[0044] N2. The preheated limestone enters the rotary kiln and decomposes into calcium oxide at 800℃-1200℃. At this temperature, the calcium carbonate in the limestone can be stably and fully decomposed, ensuring the quality and yield of calcium oxide. If the temperature is too low, the limestone will not be completely decomposed, and unreacted calcium carbonate will remain, affecting the purity and activity of subsequent calcium hydroxide. If the temperature is too high, the loss of kiln equipment will increase, increasing production costs, and also causing some side reactions, affecting the quality of calcium oxide.
[0045] N3. Calcium oxide reacts with water to obtain calcium hydroxide. The chemical process of calcium oxide reacting with water to produce calcium hydroxide is relatively simple and easy to operate. It does not require complex equipment and harsh reaction conditions, making the entire calcium hydroxide preparation process easy to control and realize industrial production in this link, reducing the difficulty of operation and management costs in the production process.
[0046] Further, the water glass comprises the following preparation steps: P1, quartz sand and soda ash are uniformly mixed in a weight ratio of 1:1.35, and the mixed raw materials are put into a high-temperature reverberatory furnace and calcined at a high temperature of 1400°C-1500°C for one hour to generate molten sodium silicate; the quartz sand and soda ash are uniformly mixed in a weight ratio of 1:1.35, which can ensure that in the subsequent high-temperature calcination process, the silicon dioxide in the quartz sand and the sodium carbonate in the soda ash can fully and completely react chemically to generate the target product molten sodium silicate, avoiding problems such as incomplete reaction or excess raw material residue caused by improper raw material ratio, thereby ensuring the purity and quality of the sodium silicate product and providing high-quality basic raw materials for the subsequent preparation of water glass.
[0047] Specifically, the high temperature of 1400℃-1500℃ can break the stable lattice structure of silicon dioxide in quartz sand and the chemical bonds of sodium carbonate in soda ash, causing the atoms and ions of the two to fully activate and recombine, and chemically react to form sodium silicate. Secondly, the one-hour calcination time ensures that the reaction has enough time to complete, so that the raw materials can be fully converted into molten sodium silicate, thereby increasing the yield of the product. Moreover, the high temperature environment of the high-temperature reverberatory furnace is relatively uniform and stable, which allows the entire raw material system to be heated evenly, avoiding local overheating or uneven reactions, and further ensuring the uniformity of the chemical composition and physical properties of the generated sodium silicate, which is conducive to subsequent processing and application.
[0048] P2. Add sodium silicate granules to the steam ball and add water to form a water glass solution. Adding sodium silicate granules to the steam ball and adding water to form a water glass solution is relatively simple and easy to operate. The steam ball provides a good reaction and mixing place. By adding water and stirring and mixing inside it, the sodium silicate granules can be quickly and evenly dissolved in water and efficiently converted into a water glass solution. This morphological transformation from solid granules to liquid solution facilitates the subsequent addition of water glass to the alkali activator in an appropriate proportion, so as to better participate in the alkali-activated reaction in the preparation process of activated slag alkali-activated concrete, and ensure that it can be evenly dispersed and play a role in the concrete system. The formed water glass solution has good fluidity and operability. Compared with solid sodium silicate, it is easier to mix with other ingredients (such as calcium hydroxide, etc.) in the alkali activator, and can better penetrate and diffuse when in contact with the mixture, so that the alkali-activated reaction is carried out more evenly in the entire concrete system.
[0049] Furthermore, another object of the present invention is to provide a composite beam made of concrete obtained by the above-mentioned method for preparing activated slag alkali-activated concrete.
[0050] Specifically, the concrete obtained by this specific preparation method utilizes the good gelling properties formed by activated slag, mineral powder and other materials under the action of alkali activators, and the internal structure is relatively dense. In the application of composite beams, this dense and high-strength concrete can effectively bear the various loads on the beam body, whether it is the vertical pressure from the upper structure, or the horizontal tension and shear force that occur during use. For example, in the composite beam structure of a bridge, it can stably support the weight of the bridge deck and passing vehicles, ensure the safety and reliability of the structure, and meet the basic strength requirements for long-term use.
[0051] Specifically, the preparation process of this concrete reduces the dependence on traditional cement, utilizes resources such as industrial by-products, and has the characteristics of good antifreeze performance and strong corrosion resistance. For composite beams, they are usually exposed to the external environment and face the influence of rain erosion, corrosion by harmful substances in the atmosphere, and temperature changes. Composite beams made of this concrete can better resist the erosion of these external factors, slow down the aging and damage of the structure, effectively extend the service life of composite beams, and reduce the cost and frequency of later maintenance.
[0052] Specifically, the composite beam uses this activated slag alkali-activated concrete, which makes effective use of a large amount of construction slag that originally needed to be landfilled, realizing the resource utilization of waste. The stock of construction slag has been increasing in the process of urbanization. The previous landfill method not only wasted land resources but also easily caused environmental problems. Now it is used as an important raw material for composite beam concrete, which greatly reduces the pressure of slag treatment and conforms to the concept of resource recycling for sustainable development. This concrete uses relatively low-cost construction slag and some industrial by-products as raw materials. Compared with the use of traditional high-quality concrete to make composite beams, it can significantly reduce the cost of raw material procurement while ensuring structural performance. In the long run, due to the good durability of composite beams made of this concrete, subsequent costs such as maintenance and replacement are reduced, and the overall cost is further reduced.
[0053] Compared with the prior art, the present invention has the following advantages: 1. The present invention provides a method for preparing activated slag alkali-activated concrete, wherein the construction slag is crushed and ground, calcined and activated, and mixed with mineral powder to form a mixture, and then mixed with sand and gravel to form alkali-activated concrete under the action of an alkali activator composed of calcium hydroxide and water glass. The alkali-activated concrete production process does not require the use of cement, and no waste is left over. It can be processed nearby without the need for external transportation or landfill, saving resources and time, and can effectively and massively solve the problem of construction waste treatment.
[0054] 2. The present invention adopts alkali-activated concrete to make composite beams, making full use of the rapid hardening and early strength properties of alkali-activated concrete to promote the sustainable development of my country's construction. BRIEF DESCRIPTION OF THE DRAWINGS
[0055] Figure 1 It is a schematic diagram of the composite beam of the present invention.
[0056] Figure 2 It is the stress cloud diagram of the composite beam of the present invention under the action of conventional load. DETAILED DESCRIPTION
[0057] In order to make those skilled in the art more clearly understand the technical solution of the present invention, the following examples are listed for illustration. Unless otherwise specified, the raw materials, reagents or devices used in the following embodiments can be obtained from conventional commercial channels or can be obtained by existing known methods.
[0058] The present invention will be further described below in conjunction with specific embodiments: The present invention adopts the following technical solutions: The method for preparing activated slag alkali-activated concrete comprises the following steps: S1. Use a crusher to break up large pieces of construction slag, and after drying, use a pulverizer to grind them into slag powder; S2, calcining the slag powder in step S1 to form activated slag, and mixing the activated slag with mineral powder and reinforcing agent to form a mixture; S3, mixing calcium hydroxide, water glass and water to form an alkaline activator; S4, premixing the mixture of step S2 and the alkali liquor activator of step S3 for 15 minutes to form a geopolymer slurry, and adding sand and gravel to stir to form concrete.
[0059] The mineral powder contains 46% calcium oxide, 24% silicon dioxide and 22% aluminum oxide.
[0060] The construction slag in step S1 is crushed to a particle size of less than 10 mm, and the slag powder is ground to a particle size of less than 0.75 mm. The crushed stone is made of granite crushed stone and slag crushed stone, which are mixed in a mass ratio of 1:1, and the crushed stone particle size is between 5-15 mm; the sand is graded sand and gravel, and the particle size is less than 3.6 mm.
[0061] The calcination method of activated slag comprises the following steps: M1. The ground slag powder is placed in a muffle furnace and heated from 20°C to 800°C at a rate of 10°C per minute, and maintained at 800°C for 2.0 hours; M2. After heating is completed, the temperature in the muffle furnace chamber is naturally cooled to 20°C to form calcined activated slag.
[0062] The activated slag, mineral powder and reinforcing agent are mixed in a mass ratio of 6:3:1 to form a mixture.
[0063] Furthermore, the weight ratio of the mixture, sand, gravel, and alkali activator is 0.8-1.2: 1.5-2.0: 2.5-3.5: 0.25-0.75, and the reinforcing agent includes at least three of carbon fiber, steel fiber, waste shell powder, rubber powder, glass fiber, retarder, and water reducer. Carbon fiber includes polyacrylonitrile-based carbon fiber or asphalt-based carbon fiber, and carbon fiber has excellent mechanical properties such as ultra-high strength and modulus. Carbon fiber evenly dispersed in concrete can effectively share the load borne by concrete like "tendons and bones", and significantly improve the mechanical properties of concrete such as tensile strength, flexural strength, and impact toughness. When the structure is subjected to tension, bending or impact, carbon fiber can inhibit the generation and expansion of cracks, enhance the overall toughness of the concrete structure, and make the structure more sturdy and durable, especially suitable for some construction projects with high requirements for earthquake and impact resistance. The addition of carbon fiber can also improve the durability and stability of concrete. It can prevent the invasion of external corrosive media such as chloride ions and sulfates to a certain extent, and delay the deterioration process of concrete. At the same time, due to its good chemical stability, it can maintain its own performance stability under complex environmental conditions, thereby improving the long-term service capacity of the entire concrete structure, reducing the number of maintenance and replacement times, and reducing the cost of the entire life cycle.
[0064] The steel fibers include corrugated steel fibers or fine steel fibers with a diameter between 0.1 and 0.3 mm.
[0065] The carbon fiber includes polyacrylonitrile-based carbon fiber or pitch-based carbon fiber having a diameter of 5-10 μm.
[0066] Waste shell powder includes oyster shells and scallop shells. The collected shells are first soaked and cleaned in 1M / L NaOH alkaline solution for 12 hours, and then the cleaned shells are broken into 200 mesh shell particles, dried, and ground into shell powder by ball milling. The powder is calcined at 800°C for 2 hours and set aside.
[0067] The rubber powder used is 80 mesh tire rubber powder processed by Shengfei Minerals.
[0068] The glass fibers include alkali-resistant glass fibers or chopped glass fibers having a diameter of 5-20 mm.
[0069] The retarder includes one of calcium ethylenediaminetetramethylenephosphonate, sodium carboxymethylcellulose and sodium gluconate.
[0070] The water reducing agent includes calcium lignin sulfonate, a polycarboxylic acid water reducing agent whose main chain is composed of a copolymer of methacrylic acid and methyl acrylate and whose side chain is polyoxyethylene.
[0071] Calcium hydroxide comprises the following preparation steps: N1. Limestone particles are sent from the raw material bin to the preheater to exchange heat with the high-temperature exhaust gas from the calcining furnace to increase the temperature of the limestone; N2, the preheated limestone enters the rotary kiln and decomposes into calcium oxide at 800℃-1200℃; N3, calcium oxide reacts with water to obtain calcium hydroxide.
[0072] Water glass comprises the following preparation steps: P1, quartz sand and soda ash are mixed evenly in a weight ratio of 1:1.35, and the mixed raw materials are put into a high-temperature reverberatory furnace and calcined at a high temperature of 1400°C-1500°C for one hour to generate molten sodium silicate; P2. Add sodium silicate granules into the steam ball and add water to form a water glass solution.
[0073] A composite beam is made of concrete obtained by the method for preparing activated slag alkali-activated concrete.
[0074] Example 1 The method for preparing activated slag alkali-activated concrete comprises the following steps: S1. Use a crusher to break up large pieces of construction slag, and after drying, use a pulverizer to grind them into slag powder; S2, calcining the slag powder in step S1 to form activated slag, and mixing the activated slag with mineral powder and reinforcing agent to form a mixture; S3, mixing calcium hydroxide, water glass and water to form an alkaline activator; S4, premixing the mixture of step S2 and the alkali liquor activator of step S3 for 15 minutes to form a geopolymer slurry, and adding sand and gravel to stir to form concrete.
[0075] The construction waste soil in step S1 is crushed to a particle size of 5 mm, and the waste soil powder is ground to a particle size of 0.5 mm.
[0076] The crushed stone is made of granite crushed stone and slag crushed stone, which are mixed in a mass ratio of 1:1, and the crushed stone particle size is 10mm; the sand is graded sand and gravel, and the particle size is 3.2mm.
[0077] The calcination method of activated slag comprises the following steps: M1. The ground slag powder is placed in a muffle furnace and heated from 20°C to 800°C at a rate of 10°C per minute, and maintained at 800°C for 2.0 hours; M2. After heating is completed, the temperature in the muffle furnace chamber is naturally cooled to 20°C to form calcined activated slag.
[0078] The activated slag, mineral powder and reinforcing agent are mixed in a mass ratio of 6:3:1 to form a mixture.
[0079] Furthermore, the weight ratio of the mixture, sand, gravel and alkali activator is 1.2:2.0:2.5:0.5. Calculated by mass, the reinforcing agent includes 5 parts of carbon fiber, 3 parts of steel fiber, 1 part of waste shell powder, 0.5 parts of glass fiber, 1 part of rubber powder and 0.2 parts of water reducer.
[0080] The steel fiber is a fine steel fiber with a diameter between 0.1-0.3 mm.
[0081] The carbon fiber is polyacrylonitrile-based carbon fiber with a diameter of 5 μm.
[0082] The glass fiber is an alkali-resistant glass fiber with a diameter of 20 mm.
[0083] The water reducer is a kind of polycarboxylic acid water reducer with the main chain being a copolymer of methacrylic acid and methyl acrylate and the side chain being a polyoxyethylene.
[0084] Calcium hydroxide comprises the following preparation steps: N1. Limestone particles are sent from the raw material bin to the preheater to exchange heat with the high-temperature exhaust gas from the calcining furnace to increase the temperature of the limestone; N2, the preheated limestone enters the rotary kiln and decomposes into calcium oxide at 1200℃; N3, calcium oxide reacts with water to obtain calcium hydroxide.
[0085] Water glass comprises the following preparation steps: P1, quartz sand and soda ash are mixed evenly in a weight ratio of 1:1.35, and the mixed raw materials are put into a high-temperature reverberatory furnace and calcined at a high temperature of 1400°C for one hour to generate molten sodium silicate; P2. Add sodium silicate granules into the steam ball and add water to form a water glass solution.
[0086] Example 2 The method for preparing activated slag alkali-activated concrete comprises the following steps: S1. Use a crusher to break up large pieces of construction slag, and after drying, use a pulverizer to grind them into slag powder; S2, calcining the slag powder in step S1 to form activated slag, and mixing the activated slag with mineral powder and reinforcing agent to form a mixture; S3, mixing calcium hydroxide, water glass and water to form an alkaline activator; S4, premixing the mixture of step S2 and the alkali liquor activator of step S3 for 15 minutes to form a geopolymer slurry, and adding sand and gravel to stir to form concrete.
[0087] The construction waste soil in step S1 is crushed to a particle size of 8 mm, and the waste soil powder is ground to a particle size of 0.7 mm.
[0088] The crushed stone is made of granite crushed stone and slag crushed stone, which are mixed in a mass ratio of 1:1, and the crushed stone particle size is 15mm; the sand is graded sand and gravel with a particle size of 2.8mm.
[0089] The calcination method of activated slag comprises the following steps: M1. The ground slag powder is placed in a muffle furnace and heated from 20°C to 800°C at a rate of 10°C per minute, and maintained at 800°C for 2.0 hours; M2. After heating is completed, the temperature in the muffle furnace chamber is naturally cooled to 20°C to form calcined activated slag.
[0090] The activated slag, mineral powder and reinforcing agent are mixed in a mass ratio of 6:3:1 to form a mixture.
[0091] Furthermore, the weight ratio of the mixture, sand, gravel and alkali activator is 0.8:1.5:2.5:0.25. Calculated by mass, the reinforcing agent includes 2 parts of carbon fiber, 5 parts of steel fiber, 1 part of waste shell powder, 1 part of glass fiber, 2 parts of rubber powder and 0.5 part of water reducer.
[0092] The steel fiber is a corrugated steel fiber with a diameter of 0.3 mm.
[0093] The carbon fiber is asphalt-based carbon fiber with a diameter of 10 μm.
[0094] The glass fibers were chopped glass fibers with a diameter of 20 mm.
[0095] The water reducing agent is calcium lignin sulfonate.
[0096] Calcium hydroxide comprises the following preparation steps: N1. Limestone particles are sent from the raw material bin to the preheater to exchange heat with the high-temperature exhaust gas from the calcining furnace to increase the temperature of the limestone; N2, the preheated limestone enters the rotary kiln and decomposes into calcium oxide at 800℃; N3, calcium oxide reacts with water to obtain calcium hydroxide.
[0097] Water glass comprises the following preparation steps: P1, quartz sand and soda ash are mixed evenly in a weight ratio of 1:1.35, and the mixed raw materials are put into a high-temperature reverberatory furnace and calcined at a high temperature of 1500°C for one hour to generate molten sodium silicate; P2. Add sodium silicate granules into the steam ball and add water to form a water glass solution.
[0098] Example 3 The method for preparing activated slag alkali-activated concrete comprises the following steps: S1. Use a crusher to break up large pieces of construction slag, and after drying, use a pulverizer to grind them into slag powder; S2, calcining the slag powder in step S1 to form activated slag, and mixing the activated slag with mineral powder and reinforcing agent to form a mixture; S3, mixing calcium hydroxide, water glass and water to form an alkaline activator; S4, premixing the mixture of step S2 and the alkali liquor activator of step S3 for 15 minutes to form a geopolymer slurry, and adding sand and gravel to stir to form concrete.
[0099] The construction waste soil in step S1 is crushed to a particle size of 3 mm, and the waste soil powder is ground to a particle size of 0.5 mm.
[0100] The crushed stone is made of granite crushed stone and slag crushed stone, which are mixed in a mass ratio of 1:1, and the crushed stone particle size is 5mm; the sand is graded sand and gravel with a particle size of 3.0mm.
[0101] The calcination method of activated slag comprises the following steps: M1. The ground slag powder is placed in a muffle furnace and heated from 20°C to 800°C at a rate of 10°C per minute, and maintained at 800°C for 2.0 hours; M2. After heating is completed, the temperature in the muffle furnace chamber is naturally cooled to 20°C to form calcined activated slag.
[0102] The activated slag, mineral powder and reinforcing agent are mixed in a mass ratio of 6:3:1 to form a mixture.
[0103] Furthermore, the weight ratio of the mixture, sand, crushed stone and alkali activator is 1.2:2.0:3.5:0.75. Calculated by mass, the reinforcing agent includes 7 parts of carbon fiber, 3 parts of steel fiber and 0.5 parts of water reducing agent.
[0104] The steel fiber is a fine steel fiber with a diameter of 0.3 mm.
[0105] The carbon fiber is polyacrylonitrile-based carbon fiber with a diameter of 5 μm.
[0106] The water reducer is a polycarboxylic acid water reducer whose main chain is a copolymer of methacrylic acid and methyl acrylate and whose side chain is a polyoxyethylene.
[0107] Calcium hydroxide comprises the following preparation steps: N1. Limestone particles are sent from the raw material bin to the preheater to exchange heat with the high-temperature exhaust gas from the calcining furnace to increase the temperature of the limestone; N2, the preheated limestone enters the rotary kiln and decomposes into calcium oxide at 800℃; N3, calcium oxide reacts with water to obtain calcium hydroxide.
[0108] Water glass comprises the following preparation steps: P1, quartz sand and soda ash are mixed evenly in a weight ratio of 1:1.35, and the mixed raw materials are put into a high-temperature reverberatory furnace and calcined at a high temperature of 1500°C for one hour to generate molten sodium silicate; P2. Add sodium silicate granules into the steam ball and add water to form a water glass solution.
[0109] Example 4 The method for preparing activated slag alkali-activated concrete comprises the following steps: S1. Use a crusher to break up large pieces of construction slag, and after drying, use a pulverizer to grind them into slag powder; S2, calcining the slag powder in step S1 to form activated slag, and mixing the activated slag with mineral powder and reinforcing agent to form a mixture; S3, mixing calcium hydroxide, water glass and water to form an alkaline activator; S4, premixing the mixture of step S2 and the alkali liquor activator of step S3 for 15 minutes to form a geopolymer slurry, and adding sand and gravel to stir to form concrete.
[0110] The construction slag in step S1 is crushed to a particle size of 6 mm, and the slag powder is ground to 0.55 mm. The crushed stone is made of granite crushed stone and slag crushed stone, which are mixed in a mass ratio of 1:1, and the crushed stone particle size is 7 mm; the sand is graded sand and gravel with a particle size of 2.5 mm.
[0111] The calcination method of activated slag comprises the following steps: M1. The ground slag powder is placed in a muffle furnace and heated from 20°C to 800°C at a rate of 10°C per minute, and maintained at 800°C for 2.0 hours; M2. After heating is completed, the temperature in the muffle furnace chamber is naturally cooled to 20°C to form calcined activated slag.
[0112] The activated slag, mineral powder and reinforcing agent are mixed in a mass ratio of 6:3:1 to form a mixture.
[0113] Furthermore, the weight ratio of the mixture, sand, gravel and alkali activator is 0.8:1.5:3.5:0.5. Calculated by mass, the reinforcing agent includes 8 parts of carbon fiber, 5 parts of steel fiber, 1 part of waste shell powder, 0.1 part of retarder and 0.2 part of water reducer.
[0114] The steel fiber is a wavy steel fiber with a diameter of 0.1 mm.
[0115] The carbon fiber is asphalt-based carbon fiber with a diameter of 5 μm.
[0116] The retarder is sodium carboxymethyl cellulose.
[0117] The water reducing agent is calcium lignin sulfonate.
[0118] Calcium hydroxide comprises the following preparation steps: N1. Limestone particles are sent from the raw material bin to the preheater to exchange heat with the high-temperature exhaust gas from the calcining furnace to increase the temperature of the limestone; N2, the preheated limestone enters the rotary kiln and decomposes into calcium oxide at 800℃; N3, calcium oxide reacts with water to obtain calcium hydroxide.
[0119] Water glass comprises the following preparation steps: P1, quartz sand and soda ash are mixed evenly in a weight ratio of 1:1.35, and the mixed raw materials are put into a high-temperature reverberatory furnace and calcined at a high temperature of 1400°C for one hour to generate molten sodium silicate; P2. Add sodium silicate granules into the steam ball and add water to form a water glass solution.
[0120] Example 5 The method for preparing activated slag alkali-activated concrete comprises the following steps: S1. Use a crusher to break up large pieces of construction slag, and after drying, use a pulverizer to grind them into slag powder; S2, calcining the slag powder in step S1 to form activated slag, and mixing the activated slag with mineral powder and reinforcing agent to form a mixture; S3, mixing calcium hydroxide, water glass and water to form an alkaline activator; S4, premixing the mixture of step S2 and the alkali liquor activator of step S3 for 15 minutes to form a geopolymer slurry, and adding sand and gravel to stir to form concrete.
[0121] The construction waste soil in step S1 is crushed to a particle size of 8.5 mm, and the waste soil powder is ground to a particle size of 0.6 mm.
[0122] The crushed stone is made of granite crushed stone and slag crushed stone, which are mixed in a mass ratio of 1:1, and the crushed stone particle size is 12mm; the sand is graded sand and gravel with a particle size of 3.0mm.
[0123] The calcination method of activated slag comprises the following steps: M1. The ground slag powder is placed in a muffle furnace and heated from 20°C to 800°C at a rate of 10°C per minute, and maintained at 800°C for 2.0 hours; M2. After heating is completed, the temperature in the muffle furnace chamber is naturally cooled to 20°C to form calcined activated slag.
[0124] The activated slag, mineral powder and reinforcing agent are mixed in a mass ratio of 6:3:1 to form a mixture.
[0125] Furthermore, the weight ratio of the mixture, sand, crushed stone and alkali activator is 1.0:1.75:3.0:0.5, and the reinforcing agent includes 4 parts of carbon fiber, 3 parts of steel fiber, 0.5 parts of waste shell powder, 1 part of rubber powder, 0.5 parts of glass fiber, 0.1 parts of retarder and 0.2 parts of water reducing agent. The steel fiber is a fine steel fiber with a diameter of 0.2 mm.
[0126] The carbon fiber is a carbon fiber with a diameter of 5 μm.
[0127] The glass fibers were chopped glass fibers with a diameter of 10 mm.
[0128] The retarder is sodium gluconate.
[0129] The water reducer is a polycarboxylic acid water reducer whose main chain is a copolymer of methacrylic acid and methyl acrylate and whose side chain is a polyoxyethylene.
[0130] Calcium hydroxide comprises the following preparation steps: N1. Limestone particles are sent from the raw material bin to the preheater to exchange heat with the high-temperature exhaust gas from the calcining furnace to increase the temperature of the limestone; N2, the preheated limestone enters the rotary kiln and decomposes into calcium oxide at 800℃-1200℃; N3, calcium oxide reacts with water to obtain calcium hydroxide.
[0131] Water glass comprises the following preparation steps: P1, quartz sand and soda ash are mixed evenly in a weight ratio of 1:1.35, and the mixed raw materials are put into a high-temperature reverberatory furnace and calcined at a high temperature of 1400°C-1500°C for one hour to generate molten sodium silicate; P2. Add sodium silicate granules into the steam ball and add water to form a water glass solution.
[0132] Comparative Example 1 The main difference between Comparative Example 1 and Example 1 is that in Comparative Example 1, the slag powder in step S1 is directly mixed with the mineral powder and the reinforcing agent to form a mixture. The remaining steps and component parameters of Comparative Example 1 are the same as those of Example 1.
[0133] Comparative Example 2 The main difference between Comparative Example 2 and Example 2 is that the mixed material of step S2 and the alkali liquor activator of step S3 are directly mixed with sand and gravel in Comparative Example 2. The remaining steps and component parameters of Comparative Example 2 are the same as those of Example 2.
[0134] Comparative Example 3 The main difference between Comparative Example 3 and Example 1 is that the reinforcing agent is directly replaced with mineral powder in Comparative Example 3. The remaining steps and component parameters of Comparative Example 3 are the same as those of Example 1.
[0135] Comparative Example 4 The main difference between Comparative Example 4 and Example 1 is that the reinforcing agent is completely replaced with carbon fiber in Comparative Example 4. The remaining steps and component parameters of Comparative Example 4 are the same as those of Example 1.
[0136] Comparative Example 5 The main difference between Comparative Example 5 and Example 1 is that the mineral powder and reinforcing agent are replaced with activated slag in Comparative Example 5. The remaining steps and component parameters of Comparative Example 5 are the same as those of Example 1.
[0137] The testing standard is the RCM method in GB / T50082-2009 "Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete" for chloride ion permeability test; GB / T50081-2019 "Standard for Test Methods of Physical and Mechanical Properties of Concrete" for compressive strength and flexural strength test. GB / T50080 is used for slump test.
[0138] The test data are shown in Table 1 and Table 2: Table 1: Performance test results of Examples 1-5
[0139] Table 2: Performance test results of comparative examples 1-5
[0140] Specifically, as can be seen from Table 1, Examples 1-5 exhibit good mechanical properties, anti-penetration properties and processing properties. Examples 1-5 provide a method for preparing activated slag alkali-activated concrete, wherein the construction slag is crushed and ground, calcined and activated, and mixed evenly with mineral powder to form a mixture, which is then mixed with sand and gravel under the action of an alkali activator composed of calcium hydroxide and water glass to form alkali-activated concrete. The alkali-activated concrete production process does not require the use of cement, and no waste is left over, and can be processed nearby without the need for external transportation or landfill, saving resources and time, and can effectively and massively solve the problem of construction waste disposal.
[0141] As can be seen from Table 2, the compressive strength and flexural strength of Comparative Example 1 are both worse than those of Example 1. Compared with Example 1, Comparative Example 1 directly mixes the slag powder in step S1 with the mineral powder and the reinforcing agent to form a mixture. The slag powder is calcined, and the calcined slag can better react with the sodium silicate and other components in the water glass to form a gel network with good adhesion and strength. Therefore, the mechanical properties and anti-permeability properties of Comparative Example 1 are worse than those of Example 1.
[0142] Comparative Example 2 Compared with Example 2, the mixture of step S2 and the alkali liquor activator of step S3 are directly stirred with sand and gravel in Comparative Example 2. Water glass can further improve the cohesiveness of the paste, and the combination of the paste and coarse and fine aggregates can make the internal structure of the concrete more compact. The mechanical properties, processing properties, and anti-penetration properties of Comparative Example 2 are worse than those of Example 2.
[0143] Comparative Example 3 Compared with Example 1, the reinforcing agent is directly replaced with mineral powder in Comparative Example 3. Among the additives, carbon fiber, steel fiber, waste shell powder, rubber powder, glass fiber, and water reducing agent can improve the mechanical properties, structural tightness, and processing performance of concrete. Therefore, the detection performance of Comparative Example 3 is worse than that of Example 1.
[0144] Compared with Example 1, Comparative Example 4 replaces all the reinforcing agents with carbon fibers. Among the added materials, steel fiber, waste shell powder, rubber powder, glass fiber, and water reducer can supplement the mechanical properties, structural tightness, and processing performance of concrete that carbon fiber cannot provide. Therefore, the detection performance of Comparative Example 4 is worse than that of Example 1.
[0145] Compared with Example 1, Comparative Example 5 replaces the mineral powder and reinforcing agent with activated slag. Since mineral powder, carbon fiber, steel fiber, waste shell powder, rubber powder, glass fiber, and water reducing agent can improve the mechanical properties, structural tightness, and processing performance of concrete relative to activated slag, the detection performance of Comparative Example 5 is worse than that of Example 1.
[0146] Example 6 It also includes a composite beam made of concrete obtained by the method for preparing activated slag alkali-activated concrete.
[0147] Alkali-activated concrete is used to make prefabricated composite beams. The commonly used cross-sectional size of composite beams is 400mmx900mm for analysis. The height of the prefabricated layer is 570mm, and the height of the cast-in-place layer is 330mm. Figure 1 As shown in the figure, alkali solution activated concrete has the characteristics of early strength, and the prefabricated composite beam can be demolded and transported in a short time. It has good fluidity and can be fully compacted when making formwork columns, which has better quality assurance.
[0148] Figure 2 This is the stress cloud diagram of the composite beam under conventional design load. The maximum compressive stress of concrete is about 11MPa, and the design value of alkali-activated concrete is 14.3>11Mpa. Alkali-activated concrete meets the structural force requirements and can be used for composite beam production.
[0149] Compared with the prior art, the invention has the following beneficial effects: it solves the waste of resources and environmental pollution caused by the transportation cost of engineering slag and landfill, and turns engineering slag into treasure. The calcination temperature of engineering slag only needs to be 800°C, which is lower than the calcination temperature of cement to reduce energy loss. After the activated slag is mixed with mineral powder and reacted with an alkali-activated solution to form a coagulant, cement is not needed to form concrete of the same strength, the cement dosage is reduced, and the damage to the environment caused by cement production is reduced, which has good social benefits.
[0150] The preparation of activated slag alkali-activated concrete can greatly reduce energy loss and reduce carbon dioxide emissions by 40% compared to ordinary cement concrete. Using it to make composite beams can meet the structural force requirements and have better durability and moldability, further promoting the development of my country's construction industrialization.
[0151] The above is a preferred embodiment of the present invention. Relevant personnel in this technical field may make several improvements and modifications without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the protection scope of the present invention.
Claims
1. A method for preparing activated soil alkali-activated concrete, characterized in that: The following steps are involved: S1. Use a crusher to break up large pieces of construction slag, and after drying, use a pulverizer to grind them into slag powder; S2, calcining the slag powder in step S1 to form activated slag, and mixing the activated slag with mineral powder and reinforcing agent to form a mixture; S3, mixing calcium hydroxide, water glass and water to form an alkaline activator; S4, premixing the mixture of step S2 and the alkali liquor activator of step S3 to form geopolymer slurry, adding sand and gravel to stir to form concrete.
2. The method for preparing activated soil alkali-activated concrete according to claim 1, characterized in that: The construction waste soil in step S1 is crushed to a particle size of less than 10 mm, and the waste soil powder is ground to a particle size of less than 0.75 mm.
3. The method for preparing activated slag alkali-activated concrete according to claim 1, characterized in that: The crushed stone is made of granite crushed stone and slag crushed stone, which are mixed in a mass ratio of 1:1, and the crushed stone particle size is between 5-15mm; the sand is graded sand and gravel, and the particle size is less than 3.6mm.
4. The method for preparing activated slag alkali-activated concrete according to claim 1, characterized in that: The calcination method of activated slag comprises the following steps: M1. The ground slag powder is placed in a muffle furnace and heated from 20°C to 800°C at a rate of 10°C per minute, and maintained at 800°C for 2.0 hours; M2. After heating is completed, the temperature in the muffle furnace chamber is naturally cooled to 20°C to form calcined activated slag.
5. The method for preparing activated slag alkali-activated concrete according to claim 1, characterized in that: Calculated by mass ratio, the ratio of calcium hydroxide, water glass and water is 10-20:40-50:30-50.
6. The method for preparing activated slag alkali-activated concrete according to claim 1, characterized in that: The activated slag, mineral powder and reinforcing agent are mixed in a mass ratio of 6:3:1 to form a mixture.
7. The method for preparing activated slag alkali-activated concrete according to claim 1, characterized in that: The weight ratio of the mixture, sand, crushed stone and alkali activator is 0.8-1.2:1.5-2.0:2.5-3.5:0.25-0.75, and the reinforcing agent includes at least three of carbon fiber, steel fiber, waste shell powder, rubber powder, glass fiber, retarder and water reducer.
8. The method for preparing activated slag alkali-activated concrete according to claim 1, characterized in that: Calcium hydroxide comprises the following preparation steps: N1. Limestone particles are sent from the raw material bin to the preheater to exchange heat with the high-temperature exhaust gas from the calcining furnace to increase the temperature of the limestone; N2, the preheated limestone enters the rotary kiln and decomposes into calcium oxide at 800℃-1200℃; N3, calcium oxide reacts with water to obtain calcium hydroxide.
9. The method for preparing activated slag alkali-activated concrete according to claim 1, characterized in that: Water glass comprises the following preparation steps: P1, quartz sand and soda ash are mixed evenly in a weight ratio of 1:1.35, and the mixed raw materials are put into a high-temperature reverberatory furnace and calcined at a high temperature of 1400°C-1500°C for one hour to generate molten sodium silicate; P2. Add sodium silicate granules into the steam ball and add water to form a water glass solution.
10. A composite beam, characterized in that: The concrete is made by using the method for preparing activated slag alkali-activated concrete as described in any one of claims 1 to 9.